The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fonc.2022.889223
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Spitz Melanocytic Lesions: From Morphologic Diagnosis to Molecular Classification

Abstract: Spitz tumors represent a distinct subtype of melanocytic lesions with characteristic histopathologic features, some of which are overlapping with melanoma. More common in the pediatric and younger population, they can be clinically suspected by recognizing specific patterns on dermatoscopic examination, and several subtypes have been described. We now classify these lesions into benign Spitz nevi, intermediate lesions identified as “atypical Spitz tumors” (or Spitz melanocytoma) and malignant Spitz melanoma. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 197 publications
(494 reference statements)
3
18
0
Order By: Relevance
“…20 Hence, IHC for BRAFV600E or genomic studies can play a significant role in solving some of these cases. 21 In deciding when ancillary studies may be indicated, there are 2 primary factors that impact the pretest probability of the lesion being a true Spitz. The first factor is age, and the second factor is how characteristically spitzoid the morphology is.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Hence, IHC for BRAFV600E or genomic studies can play a significant role in solving some of these cases. 21 In deciding when ancillary studies may be indicated, there are 2 primary factors that impact the pretest probability of the lesion being a true Spitz. The first factor is age, and the second factor is how characteristically spitzoid the morphology is.…”
Section: Discussionmentioning
confidence: 99%
“…While much more morphologic atypia, such as ulceration or brisk mitotic activity, may be tolerated in a true Spitz with a fusion driver, the same findings in a BRAF -mutated neoplasm would be much more concerning for malignancy 20 . Hence, IHC for BRAF V600E or genomic studies can play a significant role in solving some of these cases 21 …”
Section: Discussionmentioning
confidence: 99%
“…The difference was not statistically significant. Appropriate downgrades were made with the identification of pathogenic variants in HRAS or fusions typical of many desmoplastic Spitz nevi 14 as well as GNAQ/GNA11 mutations typical of many sclerosing blue nevi, in the absence of additional pathogenic variants associated with malignant transformation of these tumors. 15,16 Errant upgrades were mostly the result of 2 distinct issues, the first of which was upgrades based solely on the raw number of pathogenic variants identified.…”
Section: Discussionmentioning
confidence: 99%
“…5 In 2023, molecular categorization supports that true Spitz nevi have particular HRAS mutations or receptor tyrosine kinase translocations and lack BRAF or NRAS mutations and ancillary testing like immunohistochemistry can be supportive of (e.g., ALK immunolabeling) or disfavor (e.g., BRAF V600E immunolabeling) the diagnosis of Spitz nevus. 6 Squamous lesions, like melanocytic lesions, can pose difficulty in categorization as benign vs. malignant, with keratoacanthoma (KA) being a classic example. KA was originally described to be a benign tumor that mimics cSCC in the growth stage, but ultimately self-regresses.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Spitz nevus was originally classified as melanoma by Dr. Sophie Spitz based on histomorphologic categorization 5 . In 2023, molecular categorization supports that true Spitz nevi have particular HRAS mutations or receptor tyrosine kinase translocations and lack BRAF or NRAS mutations and ancillary testing like immunohistochemistry can be supportive of (e.g., ALK immunolabeling) or disfavor (e.g., BRAF V600E immunolabeling) the diagnosis of Spitz nevus 6 …”
Section: Introductionmentioning
confidence: 99%